Comparison of Interceptive Orthodontic Treatment Need by Professionals and Parents - Widyanto, Petronella; Yusra, Yohana (Indonesian Dental Association, 2025)
Introduction: Malocclusion is the arrangement of the teeth that is not ideal according to the dental arch. Interceptive orthodontic treatment aims to correct malocclusion during the mixed dentition period. Orthodontic index is a measuring tool to assess the severity of malocclusion, one of the indexes that can be used is Indeks Kebutuhan Perawatan Ortodonti Interseptif oleh Orang Tua (IKPOI-OT) for early detection of malocclusion in children aged 8-11 years during the mixed dentition period that can be used by parents. Objective: To determine whether there is a difference in the measurement results of the need for interceptive orthodontic treatment with IKPO-I by dentists and IKPOI-OT measured by parents at SDN Jelambar Baru 07 so that this index can be used by parents for early detection of maloclussion in children aged 8-11 years (mixed dentition period). Methods: This research is an analytical observational study with a cross-sectional design. The data obtained from the research was subjected to a statistical comparison test using the Mann Whitney test. Results: Total participants were 84 students and parents of SDN Jelambar Baru 07, the results of parent's examination showed that 55 children (65,5%) needed consultation with a dentist or orthodontist, meanwhile, the results of the dentist's examination showed that all of the children needed orthodontic treatment, 42 children (50%) needed interceptive orthodontic treatment and 42 children (50%) requires corrective orthodontic treatment. Conclusion: There is a difference in the measurement results of the need for interceptive orthodontic treatment with IKPO-I by dentists and IKPOI-OT measured by parents. Keywords: IKPO-I, IKPOI-OT, Interceptive orthodontic, Malocclusion